PELATIHAN PENGOLAHAN DODOL MANGGA UPAYA MENINGKATKAN PEMBERDAYAAN EKONOMI MASYARAKAT - Putra, Reski Praja; Sukainah, Andi; Mukhlis, Andi Muhammad Akram; Muhlis, Muhlis; Marhayati, Marhayati; Pamungkas, Satriyo (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2025)
The natural resources available in this village are seasonal tropical fruits, one of which is mango. Mangoes in this village are only used for personal consumption or directly sold to the market fresh. Utilization of mangoes through processing into products has never been done in this village. Therefore, the purpose of this community service is to provide training to farmer groups and training participants to process mangoes into mango dodol products. The method of this community service activity is a structured approach to applying science and technology to solve social problems, involving participatory methods (with the community), training and counseling. The activity begins with observation, interviews, and discussions. After that, the activity continueswith providing materials and counseling, demonstrations, mentoring, and conducting evaluations as input for improving future activities. The ingredients used in this training include sweet mango, honey mango, coconut milk, glutinous rice flour, sugar, milk, and vanilla. All of these ingredients are cooked in a pan over medium heat until the mango dodol is cooked, characterized by a soft texture and is not sticky because the surface of the dodol is oily due to the addition of coconut milk. The assessment results show that participants have been able to make mango dodol. The mango dodol produced during this training was well-liked by participants due to its high hedonic value